2019
DOI: 10.1021/jacs.9b01735
|View full text |Cite
|
Sign up to set email alerts
|

The Trans Effect in Electrocatalytic CO2 Reduction: Mechanistic Studies of Asymmetric Ruthenium Pyridyl-Carbene Catalysts

Abstract: A comprehensive mechanistic study of electrocatalytic CO2 reduction by ruthenium 2,2′:6′,2″-terpyridine (tpy) pyridyl-carbene catalysts reveals the importance of stereochemical control to locate the strongly donating N-heterocyclic carbene ligand trans to the site of CO2 activation. Computational studies were undertaken to predict the most stable isomer for a range of reasonable intermediates in CO2 reduction, suggesting that the ligand trans to the reaction site plays a key role in dictating the energetic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
122
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(133 citation statements)
references
References 59 publications
9
122
1
1
Order By: Relevance
“…An analogous trans effect, based on the influence of a trans donor ligand on the CO 2 activation bond, was recently observed for a homogeneous Ru catalyst bearing a 2,2 0 :6 0 ,2 00 -terpyridine and an asymmetric pyridyl-N-heterocyclic carbene (NHC) ligands. 348 A stereochemical control was found to be essential to efficiently catalyze CO 2 RR to CO, since the presence of the strong s-donating NHC ligand in trans to the site for CO 2 bonding significantly boosted the kinetics of the CO dissociation step. Owing to the extreme versatility of this effect, trans coordination of a tertiary amine led to a change in the selectivity of the Fe porphyrins towards formate production, contributing to facilitate the protonation of reduced CO 2 as well as the formate release step (vide supra).…”
Section: Fe-n-c Catalystsmentioning
confidence: 99%
“…An analogous trans effect, based on the influence of a trans donor ligand on the CO 2 activation bond, was recently observed for a homogeneous Ru catalyst bearing a 2,2 0 :6 0 ,2 00 -terpyridine and an asymmetric pyridyl-N-heterocyclic carbene (NHC) ligands. 348 A stereochemical control was found to be essential to efficiently catalyze CO 2 RR to CO, since the presence of the strong s-donating NHC ligand in trans to the site for CO 2 bonding significantly boosted the kinetics of the CO dissociation step. Owing to the extreme versatility of this effect, trans coordination of a tertiary amine led to a change in the selectivity of the Fe porphyrins towards formate production, contributing to facilitate the protonation of reduced CO 2 as well as the formate release step (vide supra).…”
Section: Fe-n-c Catalystsmentioning
confidence: 99%
“…In recent years, computational study of the catalytic reactions has drawn significant attention from the researchers to confirm the experimental results, and to find a good relationship between the structures and properties of catalysts . Therefore, the theoretical calculations were performed to confirm the proposed electrocatalytic cycle for the CO 2 reduction to CO in the presence of cis ‐[Ru (Me 4 phen) 2 (CH 3 CN) 2 ](PF 6 ) 2 .…”
Section: Resultsmentioning
confidence: 99%
“…47 We have also shown that reticular materials can influence CO 2 selectivity and activity by electronic delocalization in the secondary coordination sphere. [48][49] Redox-active ligands based on polypyridines, [50][51][52][53][54][55] imines, 56 and porphyrins [57][58] can also be employed for CO 2 reduction, where ligand-centered reductions offer the advantage of removing electron density away from the metal center to diminish metal hydride formation and off-pathway H 2 evolution. 59 Our laboratory and Miller's laboratory have identified molecular terpyridine-based iron complexes that are highly active CO 2 -to-CO electrocatalysts that operate at extremely low overpotentials due to electronic delocalization.…”
Section: Introductionmentioning
confidence: 99%